Pengembangan Media Monopoli Matematika pada Materi Peluang untuk Siswa SMP - Deviana, Desya Rossa; Prihatnani, Erlina (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2018)
This study aims to develop Monopoly Mathematics Media (Monomath) to learning mathematical probability exercises at junior high school. Using the ADDIE model consist of five phases - Analyze, Design, Development, Implementation, and Evaluation to develop this Monomath Media. This Monomath has gone through validity, practicability, and effectiveness test. The result of this research showed that the Monomath obtained a total average score for all aspect were 78.1% of validity matter expert and 80.8% of validity media expert, which means the media is valid. In the feasibility, the study result obtained a total average score for all aspect was 82.5%, which means the media has met practical criteria. The field trials result were obtained an average score of 95.46 for the posttest. It is higher than pretest average score was 54.83. The result of the student questionnaire showed that an average score of 90% which means the student give a positive response to the Monomath they used. Thus, the result of Monomath to learning mathematical probability is valid, practical, and effective.